Melanocytic naevi with globular and reticular dermoscopic patterns display distinct BRAF V600E expression profiles and histopathological patterns. (1st November 2014) - Marchetti, M.A.; Kiuru, M.H.; Busam, K.J.; Marghoob, A.A.; Scope, A.; Dusza, S.W.; Cordova, M.A.; Fonseca, M.; Wu, X.; Halpern, A.C.
Summary: Background: BRAF ( v‐raf murine sarcoma viral oncogene homologue B ) V600E mutations have been detected with high frequency in melanocytic naevi. Few studies have stratified analyses by naevus dermoscopic pattern. Objectives: To determine the frequency of BRAF V600E expression and histopathological pattern in acquired melanocytic naevi distinguished by a globular vs. reticular dermoscopic pattern. Methods: We retrospectively identified histologically proven melanocytic naevi with banal reticular or globular dermoscopic patterns and evaluated BRAF V600E expression using immunohistochemistry. Results: BRAF V600E expression was detected in 11 of 12 globular naevi vs. four of 13 reticular naevi (91·7% vs. 30·1%, P = 0·004). A predominantly dermal growth pattern ( P < 0·001) and the presence of large junctional nests ( P = 0·017) were each associated with a globular dermoscopic pattern. The presence of either a predominantly dermal growth pattern or large junctional nests was found in 13 of 15 naevi positive for BRAF V600E and in two of 10 naevi negative for BRAF V600E (86·7% vs. 20%, P = 0·002). Conclusions: The frequency of BRAF V600E mutations differs in naevi distinguished by unique dermoscopic structures and microanatomical growth patterns. Globular naevi, which most often histologically correspond to a predominantly dermal growth pattern and/or the presence of large junctional nests, are significantly more likely to express BRAF V600E than reticular naevi. These preliminary results require validation, but may directly inform future studies of naevogenesis and melanoma genesis.